39 A Model of Gait and Falls in Older Adults with Dementia. (20th December 2019) - Zhang, Weihong; Low, Lee-Fay; Schwenk, Michael; Mills, Nicholas; Gwynn, Josephine Diana; Clemson, Lindy
Abstract: Background: Older people with cognitive impairment are at increased risk of falls; however, fall prevention strategies have limited success in reducing fall risks in this population (Fernando E, Fraser M, Hendriksen J et al. Physiotherapy Canada. 2017; 69: 161–170). We aim to present a model of factors contributing to gait and falls in older adults with dementia. Methods: The model was developed based on an in-depth review of literature on fall risk factors particularly in people with dementia, and the relationship between cognition and gait, and their joint impact on risk of falls. Results: Cognitive and motor functions are closely related as they share neuroanatomy (Rosso AL, Studenski SA, Chen WG et al. J Gerontol A Biol Sci Med Sci. 2013; 68: 1379–1386). This close relationship has been confirmed by imaging, observational and interventional studies. Executive function is the cognitive domain most commonly associated with gait dysfunction (Cohen JA, Verghese J, Zwerling JL. Maturitas. 2016; 93: 73-77). The sub-domains of executive function(Sachdev PS, Blacker D, Blazer DG et al. Neurology. 2014; 10: 634-642) - attention, sensory integration and motor planning affect risk of falls through gait dysfunction; whereas other non-gait associated sub-domains of executive function - cognitive flexibility, judgement and inhibitory control affect risk of falls through risk taking behaviour. Conclusion: Gait, cognition and falls are closely related. The comoridity and interaction between gait abnormality and cognitive impairment may be the underlying mechanism behind the high prevalence of falls in older adults with dementia. Gait and cognitive assessment with particular focus on executive function, should be integrated in fall risk screening. Assessment results should inform interventions developed by a multidisciplinary team and may include strategies such as customised gait training and behavioural modulation. A comprehensive multidisciplinary approach could be more effective in reducing fall risks in older adults with dementia.